2021
DOI: 10.1021/acssuschemeng.0c07470
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Extraction and Recovery of Cobalt from Simulated Solution of Spent Ternary Lithium Batteries Using the Novel Ionic Liquids of [C8H17NH2][Cyanex 272]

Abstract: An environmentally friendly recycling process of cobalt (Co2+) from simulated solution for spent ternary lithium batteries was demonstrated in this research. The novel task-specific ionic liquids (TSILs) of [C8H17NH2]­[Cyanex 272] were synthesized by one-step reaction of n-octylamine and Cyanex 272. The TSILs have good performance for selective extraction and separation of Co2+. The separation factor of Co2+ and Ni2+ (βCo/Ni) was 976.9 using the two-stage cross-flow extraction, and the extraction percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…In the case of metal extraction with ILs, the list is too long; several elements are studied with these green reagents, for example, molybdenum, rare earth, precious metals, chromium, iron, copper, cobalt, lead, and zinc [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of metal extraction with ILs, the list is too long; several elements are studied with these green reagents, for example, molybdenum, rare earth, precious metals, chromium, iron, copper, cobalt, lead, and zinc [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Jing and coworkers recovered cobalt selectively from lithium batteries using the ionic liquid [C 8 H 17 NH 2 ] [Cyanex 727]. The system has a good performance and produces a final product CoSO 4 × 7H 2 O, with high purity (99.7%) [24]. Rybka and Regel-Rosocka report Ni(II) and Co(II) extraction with the use of Cyphos IL 101 and Cyphos IL 104 in chloride media.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] For example, Jing et al reported a novel ionic liquid [C 8 H 17 NH 2 ][Cyanex272], which was synthesized using n-octylamine and Cyanex 272, for the recovery of cobalt from a simulated solution of spent ternary lithium batteries. 37 The nitrogen atoms of n-octylamine combined with the H + provided by Cyanex 272, then the cation [C 8 H 17 NH 3 ] + was formed. Recently, studies that report that amides constitute the cations of protic ILs have gradually aroused the interest of researchers.…”
Section: Resultsmentioning
confidence: 99%
“…After single-stage extraction, the TSIL-based extraction phase containing Co[Cyanex 272] 2 can be stripped with 0.5 mol/L H 2 SO 4 ( Figure 7 ). The stripping percentage of Co 2+ from TSIL-based extraction phase was about 99.2% with the optimized stripping conditions, i.e., stripping phase ratio of 1:1, stripping time of 35 min, and stripping temperature of 308 ± 1 K. The product of CoSO 4 ·7H 2 O was obtained from the stripping phase using evaporation crystallization [ 44 ]. The product of Ni(OH) 2 can be obtained from the raffinate of the aqueous phase containing Ni 2+ using the precipitation method [ 45 ].…”
Section: Resultsmentioning
confidence: 99%